Pengaruh Kualitas Pelayanan dan Harga Terhadap Keputusan Penggunaan GoRide dan GrabBike di Yogyakarta - Elfa Fachrida Mahasani; Tri Harsini Wahyuningsih (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
Abstract This study aims to examine the effect of service quality and price on the decision to use GoRide and GrabBike in Yogyakarta. Data were collected using a questionnaire. The population in this study were all GoRide or GrabBike users in Yogyakarta. The samples in this study were 130 GoRide users and 130 GrabBike users, which were taken using a simple random sampling method. The data analysis technique used is multiple linear regression analysis and compare means. The results showed that partially, service quality had a positive and significant effect on the decision to use GoRide, but had no effect on GrabBike users. Price has a positive and significant effect on decisions to use GoRide and GrabBike. The results of the compare means test show that there are no differences in the factors that influence the decision to use GoRide or GrabBike in Yogyakarta.